Physical activity is associated with lower arterial stiffness in normal‐weight postmenopausal women. Issue 9 (20th August 2020) - Stamatelopoulos, Kimon; Tsoltos, Nikolaos; Armeni, Eleni; Paschou, Stavroula A.; Augoulea, Areti; Kaparos, Georgios; Rizos, Demetrios; Karagouni, Iliana; Delialis, Dimitris; Ioannou, Sophia; Apostolakis, Michail; Makrakis, Evangelos; et al.
Abstract: The impact of physical exercise, as preventative measure, to control the progression of cardiovascular disease in midlife remains under investigation. We aimed to investigate the effect of different levels of intensity of physical activity on metabolic and vascular profile in healthy postmenopausal women. A total of 625 healthy postmenopausal women (mean age 57.7 ± 7.6 years) were evaluated using the short IPAQ questionnaire for quantification of physical activity. The energy expenditure was estimated in metabolic equivalent of energy (MET) hours per week. Pulse wave velocity (PWV) was measured as an index of arterial stiffness. Intima‐media thickness of both right and left common carotid artery, carotid bulb and internal carotid artery, and combined carotid IMT were also assessed by non‐invasive and well‐validated methods. Mean values of PWV decreased linearly with increasing intensity of physical activity (classes of physical activity: sedentary vs walking vs moderate vs vigorous activity: 9.07 ± 1.22 m/s vs 9.12 ± 1.72 m/s vs 8.47 ± 1.31m/s vs 7.94 ± 0.40 m/s, ANOVA P for linear trend .003). In non‐obese postmenopausal women, PWV values associated with: (a) the total number of METs (b‐coefficient = −0.261, P = .002) as well as with SBP; (b) or with the number of moderate METs (b‐coefficient = −0.192, P = .025) as well as with age and SBP. No significant associations were observed between the intensity of physical exercise and arterial stiffness in the overweight‐obese group. Physical activity is negatively associated with arterial stiffness in postmenopausal women with normal weight. This association was not observed in overweight or obese women.